Aktivitas Antiinflamasi Gel Cabai Rawit (Capsicum frutescens L.) pada Tikus Putih (Rattus norvegicus) - Rahmat Ismail; Abulkhair Abdullah; Ahlan Sangkal; Randi R. Toboleu (JURNAL FARMASI DAN MAKANAN, 2022)
Cayenne pepper (Capsicum frutescens L.) is a plant that has many benefits, one of which is as an anti-inflammatory. The anti-inflammatory effect of cayenne pepper was tested on white rats in the form of a gel. Two gel formulas were used with different concentrations of propylene glycol as additive, 25% and 30%, respectively. White rats were grouped into 4 groups, negative control group (gel base), positive control group (Voltaren® Emulgel), gel formula 1 group (enhancer 25%), and gel formula 2 (enhancer 30%). Albumen was induced on the backs of white rats then samples were given. Skinfold thickness measurements were taken every 1 hour for 6 hours. The data obtained in the form of skin thickness values ​​(mm). The % Inflammation Inhibition (% PI) was calculated for each sample. Formula 1 and Formula 2 gave %PI of 32.58 ± 1.80 and 40.75 ± 5.71, respectively. Both formulas had an anti-inflammatory effect against edema on the back of rats although not better than Voltaren® Emulgel. Based on One Way ANOVA test, Formula 2 has a better anti-inflammatory effect than Formula 1. LSD test results show that %PI Formula 2 is similar to %PI Voltaren® Emulgel with a significance value of 0.117 (>0.05).